Advancing agroecology and dietary diversity in Vihiga: Bioversity International's instrumental collaboration on the county's first agroecology policy 2024 - Oduor, Francis Odhiambo; Termote, Celine; Aluso, Lillian Olimba; Induli, Irene Mudiovo (2025)
In August 2024, the County Government of Vihiga launched a public consultation on its new Agroecology Policy, developed with the active participation of Bioversity International. Over the past decade, Bioversity International has facilitated an integrated community-based approach, leading to the establishment of a community seed bank in Vihiga for traditional leafy vegetables, benefitting 8,500 farmers. As a result, 85% of Vihiga County farmers diversified their farms and 75% reported better diets and incomes, ultimately influencing the design of the county-level Agroecology Policy [13,14,18,19].